La reforma del proceso penal en España (2005)
This article deals with the reform of the Spanish criminal justice, which began almost 20 years ago from the emergence of democracy and the Constitutional Text of 1978 in force and has been a majority restoration or vindication of the specialized doctrine and society itself.No one approaching the situation of our criminal justice with a minimum of objectivity can disagree with the need of this reform that, in a partial way, has been carried out in the most recent amending legislative initiatives to the Criminal Indictment Law ( Ley de Enjuiciamiento Criminal ), with technical solutions that turn to be almost evident for themselves. Perhaps better than any other legislative initiative of all those having emerged from the State Covenant for the Reform of Justice ( Pacto de Estado para la Reforma de la Justicia ), the socalled Fast Judgment Act ( Ley de Juicios Rápidos 38/2002 of October 24) of Amendment of the Criminal Indictment Law ( Ley de Enjuiciamiento Criminal ) and its supplementary L.O. 8/2002, summarizes the two great objectives designed by the Ministry of Justice: On the one hand, modernizing the Spanish administration of justice by making it more agile, efficient, transparent and close to the citizens and, on the other hand, invigorating the judicial system as a whole as an essential base instrument of the fight against criminality.It has been intended, from some sectors, to convey to the juridical community the idea that the slowness seen in criminal instruction brings guarantees to the accused. However, we understand that the delay of several weeks or even months it takes has nothing to do with the guarantees of procedure inherent to the due process of law, the intimate constitutional value of which (the socalled principle of procedure that so industrially builds the doctrine of the US Supreme Court from the XVI Amendment) we must not pervert. We neither believe that it brings any advantage to the accused or the victims or those third parties having to take part in the criminal process, the indefinite prolongation of the middle phase of the procedure or the severalmonth delay (between three and five on average) in the determination of the oral hearing, as it has been occurring.Concern about some kind of justice administration where speed is made one of its main informative principles is a historical constant in our country.The Criminal Indictment Law itself in its original wording (more than 120 years ago) did already incorporate certain precepts where the acceleration principle was included, leading to avoid unjustified delays in criminal procedures, as inferred from some of its legal statements.The last great amendment or reform of the Criminal Indictment Law ( L.E. Criminal ) carried out, as already said, by Act [ Ley ] 38/2002 under the aforementioned State Covenant for the Reform of Justice, should the modernization process of the major procedural laws be completed, by placing among its aims the speeding up of procedures, is not, as it has been indicated as well, a new end within the Spanish criminal indictment frame. Certainly, lack of reforms attached to this same objective cannot be adduced.Nonetheless, global experience arising under each one of these legislative novelties, though all of them contributed positive aspects, cannot be deemed satisfactory in exact terms. Sometimes, routine in the applicative processes of procedural standards and lack of resources to consolidate some of the most important events contributed to promote more skepticism about the likely actual solution to the problem of immediate indictment with respect to mild infractions that those intended by the most recent reforms that we will analyze.However, as we will see when approached, the promulgation of a new Criminal Code of Procedure ( Código Procesal Penal ) has become essential because the nineteenth Criminal Indictment Law does not admit any more amendments, patches, or partial reformations, many of which do frontally clash, as we will see, with the informative principles of the system established therein.